Evaluation of direct-quadrature position and saturation of a SynRM machine with segmented rotor - Anwar, M. Shahril; Rasid, Mohd Azri Hizami (Penerbit UMP, 2022)
The synchronous reluctance machine has gained popularity in traction and other smaller application thanks to its design that need very little or even no permanent magnet. Without internal permanent magnet assistance, an adequate level of torque density could be achieved by having an optimized rotor design to attain the optimum ratio of direct inductance over quadrature inductance. In order to properly control the machine, the direct and quadrature position need to be identified. In this study, a segmented rotor topology without permanent magnet was chosen. We evaluate the direct and quadrature position of the rotor topology, its saturation level and provide the flux linkage and the inductances of the machine.